Benefits and harms associated with hormone replacement therapy: clinical decision analysis. Issue 7436 (12th February 2004) - Minelli, Cosetta; Abrams, Keith R; Sutton, Alex J; Cooper, Nicola J
Abstract: Objective To evaluate harms and benefits associated with use of combined hormone replacement therapy (HRT) for five years in women with different baseline risks for breast cancer. Design Probabilistic clinical decision analysis. Setting Hypothetical population of white UK women aged 50 years with different baseline risks for breast cancer. Main outcome measure Gain or loss in quality adjusted life years (QALYs). Results Women free of menopausal symptoms showed a net harm from HRT use, which increased for increasing baseline risk of breast cancer. Those with a baseline risk of 1.2% would expect a loss in QALYs of 0.4 months (- 0.03 QALYs, 95% credibility interval - 0.05 to - 0.01). The main analysis showed HRT to be on average beneficial in women with symptoms, with benefit decreasing with increasing baseline risk of breast cancer. The results were sensitive to the assumed value of quality of life with menopausal symptoms, therefore a contour plot was developed to show the probability of net harm for a range of different values and baseline risks. Conclusions HRT for primary prevention of chronic diseases in women without menopausal symptoms is unjustified. Perceived quality of life in women with symptoms should be taken into account when deciding on HRT. Thus, a decision analysis tailored to an individual woman is more appropriate in clinical practice than a population based approach.